The Impact of Changes in Globalization of Life in Indonesia - Miftahul Jannah Hasibuan; Nuri Aslami (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
Globalization is the linkage and dependence between nations and between people around the world through trade, investment, travel, popular culture, and other forms of interaction so that the boundaries of a country become increasingly narrow. The formulation of the problem in writing this scientific paper is, "How is the impact of globalization on the life of the Indonesian people? The purpose of writing this scientific paper is to describe the impact of globalization on the life of the Indonesian people. The approach is qualitatively descriptive. Globalization is physically marked by the development of cities that are part of the world city network. This can be seen from the telecommunications infrastructure, transportation network, international scale companies and their branches. The positive impact of globalization is a change in values and attitudes, the development of science and technology, a better level of life.